2021
DOI: 10.21037/qims-20-1378
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the histological invasiveness of pulmonary adenocarcinoma manifesting as persistent pure ground-glass nodules by ultra-high-resolution CT target scanning in the lateral or oblique body position

et al.

Abstract: Background: Ultra-high-resolution computed tomography (U-HRCT) has improved image quality for displaying the detailed characteristics of disease states and lung anatomy. The purpose of this study was to retrospectively examine whether U-HRCT target scanning in the lateral or oblique body position (protocol G scan) could predict histological invasiveness of pulmonary adenocarcinoma manifesting as pure groundglass nodules (pGGNs). Methods: From January 2015 to December 2016, 260 patients with 306 pathologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Hsu et al reported that the mean diameter of IA was significantly higher than that of AIS/MIA ( 16 ). In the study of Ren et al , the maximum diameter could differentiate between IAs and preinvasive lesions ( 17 ). Furthermore, we also verified the predictive value of the critical value of −415 HU in small size lung nodules with a maximum diameter ≤10 mm, showing satisfactory sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al reported that the mean diameter of IA was significantly higher than that of AIS/MIA ( 16 ). In the study of Ren et al , the maximum diameter could differentiate between IAs and preinvasive lesions ( 17 ). Furthermore, we also verified the predictive value of the critical value of −415 HU in small size lung nodules with a maximum diameter ≤10 mm, showing satisfactory sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative assessment was undertaken by 2 independent radiologists (J.P. and S.C.) who were blinded to the diagnosis and the other reader’s result. Qualitative features including lobulation, spiculation, bubbly lucency, adjacent cystic airspace, dilated air-bronchogram, vessel change, and pleural retraction were assessed as previously described 9,19-22 (Figure 1), and the qualitative features are described in the Supplementary Methods.
Figure 1.Qualitative features of pure ground-glass nodules on thin-section computed tomography images. (A) Lobulation in a 78-year-old woman with minimally invasive adenocarcinoma (MIA).
…”
Section: Methodsmentioning
confidence: 99%
“…This classification has important prognostic implications because preinvasive lesions like AAH, AIS, and MIA have a more favorable prognostic outcome than IPA lesions (9)(10)(11). As persistent SSNs have a higher likelihood of lung adenocarcinoma spectrum lesions with heterogeneous growth or aggressive behavior, it is important for radiologists and clinical physicians to correctly identify these indolent preinvasive lesions from IPAs preoperatively (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%